2006
DOI: 10.1080/15287390500196081
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Burst: Role in Signal Transduction in Alveolar Macrophages

Abstract: Alveolar macrophages play an important role in defense against airborne pathogens and particles. These macrophages respond through both the adaptive and acquired immune responses, and through the activation of a multitude of signaling pathways. One major macrophage defense mechanism is respiratory burst, the production of reactive oxygen species (ROS). While the ROS produced may act directly in pathogen killing, they may also be involved as secondary signaling messengers. This review focuses on the activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 76 publications
2
95
0
1
Order By: Relevance
“…[42][43][44] Under these stimuli (IFN-g or LPS), we detected increased levels of NBS1. In Nbs1 ΔB/ΔB macrophages, this stimulation led to increased DNA damage that could be strongly reduced by the addition of N-acetyl-L-cysteine, indicating that the MRE11 complex was important for suppressing ROS-induced DNA damage ( Figure 1D).…”
Section: Discussionmentioning
confidence: 77%
“…[42][43][44] Under these stimuli (IFN-g or LPS), we detected increased levels of NBS1. In Nbs1 ΔB/ΔB macrophages, this stimulation led to increased DNA damage that could be strongly reduced by the addition of N-acetyl-L-cysteine, indicating that the MRE11 complex was important for suppressing ROS-induced DNA damage ( Figure 1D).…”
Section: Discussionmentioning
confidence: 77%
“…Cross-talk between lung epithelial cells and alveolar macrophages is known to inhibit the latter's inflammatory properties [43,44]. Although alveolar macrophages are quiescent under steady-state conditions, they can be activated by extrinsic and intrinsic stimuli and then participate in phagocytosis, bacterial killing and tissue wound healing [45,46]. As seen in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the signal transduction mechanism of macrophage activation have indicated that stimuli, such as LPS or IL-4, trigger the mitogenactivated protein kinase (MAPK) and phosphoinositol-3-kinase (PI3K) signaling pathways [20,21] . MAPK pathway positively regulated the expression of proinflammatory cytokines (TNF-α, IL-1β, IL-6 etc), whereas PI3K pathway conversely inhibits MAPK pathway activation and induced anti-inflammatory cytokines (IL-10 etc) [22,23] .…”
Section: Introductionmentioning
confidence: 99%